Green SDN: Trends of Energy Conservation in Software Defined Network - Jeyasekar, A; Nanda, Siddharth; Uthra, Annie (International Journal of Engineering and Technology, 2018)
Because of the exponential growth of the data in the Internet, storing and computing the data become a challenging issue. Therefore the data center networks are used to provide the infrastructure for storing and computing the data. Most of the network devices present in the data center network is comparatively idle for most of the time and resulting in a waste of energy. To overcome it, the Software Defined Network is proposed which allows the administrators to manage the network devices using a centralized controller and enables programmable network devices. It optimizes the utilization of network resources efficiently and results in significant amount of energy saving. There are several approaches proposed for optimizing the energy in the Software Defined Network which takes a network towards green energy and lower carbon print. This paper presents a survey on energy conservation techniques used in the software defined networks which makes the networks more capable and productive. We also provide a brief comparison of possible energy conservation techniques and guidelines for future research. Â Â